‘Welas Asih Diri’ dan ‘Bertumbuh’: Hubungan Self-Compassion dan Flourishing pada Mahasiswa - Zulfa, Nuril Aziqah; Prastuti, Endang (Mediapsi, 2020)
College students face various challenges, strains and failures, which could prevent them from achieving a higher state of flourishing. The purpose of this study was two-fold. The first was to describe students’ self-compassion and flourishing, whereas the second was to examine the correlation between self-compassion and flourishing among a sample of students from the State University of Malang. The sample consisted of 160 students from eight faculties who were selected through cluster sampling. Self-compassion and flourishing were both self-developed by the authors. The main finding demonstrated that in line with the hypothesis, high levels of self-compassion are associated with high levels of flourishing. Mahasiswa dihadapkan pada berbagai tantangan, tekanan dan kegagalan yang dapat menghalangi mereka untuk mencapai flourishing yang lebih tinggi. Penelitian ini bertujuan untuk mengetahui gambaran self-compassion dan  flourishing, serta hubungan antara self-compassion dan flourishing pada mahasiswa Universitas Negeri Malang. Sampel dalam penelitian ini terdiri dari 160 mahasiswa dari 8 fakultas yang dipilih dengan menggunakan teknik cluster sampling. Pengumpulan data dengan menggunakan skala self-compassion dan skala flourishing yang dikembangkan oleh penulis. Hasil penelitian menunjukkan bahwa, sesuai dengan hipotesis yang ditetapkan, tingginya self-compassion berasosiasi dengan tingginya flourishing pada mahasiswa.